Dietary Phyllanthus Emblica inclusion regulates growth, serum biochemistry, organ histology, gene expression, and resistance against Aspergillus Flavus in Nile Tilapia (Oreochromis Niloticus) - Samyah D. Jastaniah; Najah M. Albaqami (Scientific Reports)
Abstract This research aimed to explore the effect of Phyllanthus emblica powder on the growth performance, blood hematology, body composition, serum biochemistry, organ histology, gene expression and resistance of Nile Tilapia (Oreochromis niloticus) against Aspergillus flavus. A total of 240 fish (30.5 ± 2.0 g) were distributed in 12 ponds with 20 fish per pond and fed a basal diet supplemented with 0, 1%, 2% and 3% of P. emblica powder for 60 days. A challenge experiment was performed at the end of the trial. All supplemented groups showed better growth performance (final body weight, weight gain, and specific growth rates) (P < 0.05), while feed intake did not affect (P > 0.05). The feed conversion ratio enhanced by the inclusion of dietary P. emblica (P < 0.05). In terms of body composition, crude lipids decreased, while ash percentages increased after fish were fed with P. emblica (P < 0.05). Liver function decreased significantly, while protein fraction, blood hematology and digestive enzymatic profile (amylase, and lipase) were significantly increased in all treated groups. Fish fed with P. emblica exhibited a higher survival rate and increased resistance to A. flavus compared to the control diet. Diets containing P. emblica improved the histoarchitecture of hepatopancreatic and intestine of Nile Tilapia. The inclusion of P. emblica significantly upregulated the expression of CC chemokine, IL-1β, IL-8, SOD, and GPx genes, with a gradual increase in P. emblica levels in the diet (P < 0.05). In conclusion, dietary supplementation with P. emblica powder may serve as an effective strategy for promoting growth and acting as an immunostimulant in Nile Tilapia aquaculture.